2016
DOI: 10.1259/bjr.20160641
|View full text |Cite
|
Sign up to set email alerts
|

Current status of kilovoltage (kV) radiotherapy in the UK: installed equipment, clinical workload, physics quality control and radiation dosimetry

Abstract: Objective: To assess the status and practice of kilovoltage (kV) radiotherapy in the UK. Methods: 96% of the radiotherapy centres in the UK responded to a comprehensive survey. An analysis of the installed equipment base, patient numbers, clinical treatment sites, quality control (QC) testing and radiation dosimetry processes were undertaken. Results: 73% of UK centres have at least one kV treatment unit, with 58 units installed across the UK. Although 35% of units are over 10 years old, 39% units have been in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The use of kilovoltage allows for a more predictable dosimetry compared to radioactive isotopes and eliminates the unnecessary exposure of patients and health personnel to ionising radiation. To date, our Institution has replaced the use of isotopes for surface treatment, in line with the international trend towards migration to more secure systems of treatment, which allow for versatility in pathology management of other anatomical regions [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of kilovoltage allows for a more predictable dosimetry compared to radioactive isotopes and eliminates the unnecessary exposure of patients and health personnel to ionising radiation. To date, our Institution has replaced the use of isotopes for surface treatment, in line with the international trend towards migration to more secure systems of treatment, which allow for versatility in pathology management of other anatomical regions [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Surveys have been a useful tool in understanding and documenting the standard‐of‐care in various topics in radiotherapy physics . Over the past 5 yr, there have been over 250 surveys distributed mainly through the medical physics listserv covering varying topics of interest to clinical physicists (e.g., simulation practices, use of image guidance, and clinical workflow).…”
Section: Introductionmentioning
confidence: 99%
“…A survey of practice in the UK from 2015 found that 27% of centres had no kilovoltage unit [20]. The main reasons given for this absence was the use of electrons or HDR brachytherapy instead, and insufficient patient numbers.…”
Section: Opening Statementmentioning
confidence: 99%